Living wounds (anfechtungen) or blacksmithing of the human soul? The pastoral art of marvellous exchange (mirifica commutatio) in spiritual well-being - D.J. Louw (Acta Theologica)
Many of the unexpected, undeserved forms of suffering and the constant exposure to human brokenness infiltrate schemata of interpretation and frameworks of meaninggiving, causing guilt, doubt, torment, and anguish – a kind of paralysis of the human soul; the hopelessness of désespoir (the nausea of unhope). Instead of blacksmithing spiritual pathology (spiritual victimisation by means of punishment and self-blame), an approach of living wounds is proposed, namely to embrace them within the process of reaching out to the wounds of the other. Within the framework of Christian theology, the healing dimension of a theologia crucis is researched. In this regard, the notion of mirifica commutatio (marvellous exchange) in Martin Luther’s understanding of a “suffering God” is discussed as an illustration of what thehealing of externalisation in pastoral caregiving entails. Thus, the emphasis on divine substitution in a pastoral approach of “double switching”, while facing the factuality of the irreversibility of Anfechtungen (spiritual dread and anguish) and human imperfection.